Engineering sustainability practical guide for sustainable design - Jonker, Gerald (Elservier, 2012)
This book provides engineer with the nessary information to design sustainable processes,product and value chain. Its describe the current consensus on sutainable development for four context levels. Planet ,society business and engineers. It also present all required design steps.